1995
DOI: 10.1109/50.400721
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging of annealed proton-exchanged waveguides

Abstract: Abstrucf-Low temperature hydrogen diffusion in annealed proton-exchanged (APEm) waveguides has the potential of degrading device performance over a period of several years. An accelerated aging study was performed in order to determine its impact on device performance. The effect of aging was modeled as a second anneal. Both planar waveguides and Yfed Balanced-Bridge Modulator (YBBM) devices were aged at elevated temperatures. The hydrogen concentration profde of the planar waveguides was measured after aging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…The annealing process successfully addresses the problems of index instability [9], [10] and deterioration of the electrooptic effect [11] exhibited by proton-exchanged waveguides without anneal. Accelerated aging studies carried out on x-cut APE directional couplers and Mach-Zehnder modulators have shown no degradation of device performance over a 13-year lifetime at 125 C and a 25-year lifetime at 95 C [12], [13].…”
Section: B Waveguide Fabricationmentioning
confidence: 99%
“…The annealing process successfully addresses the problems of index instability [9], [10] and deterioration of the electrooptic effect [11] exhibited by proton-exchanged waveguides without anneal. Accelerated aging studies carried out on x-cut APE directional couplers and Mach-Zehnder modulators have shown no degradation of device performance over a 13-year lifetime at 125 C and a 25-year lifetime at 95 C [12], [13].…”
Section: B Waveguide Fabricationmentioning
confidence: 99%
“…The mathematic model of Y waveguides' degradation mechanism is built in [12], and how the measure parameters outside reflect tthis mechanism inside is deduced, which is completed and convincing.…”
Section: )mentioning
confidence: 97%
“…Os íons de hidrogênio do banho e os íons de Li do cristal migram, aumentando a concentração de prótons no cristal e reduzindo a concentração de Li. O processo PE, em ácido benzóico puro, resulta em um aumento de aproximadamente 0,12 no valor do índice de refração extraordinário do LiNbO 3 , para λ = 0,6328 µm, enquanto o índice ordinário permanece praticamente inalterado [136] - [138]. Além disso, há uma redução nos coeficientes eletroópticos e as perdas por propagação aumentam [139].…”
Section: A Modelos Que Relacionam Concentração De Prótons E íNdice Dunclassified